Modelling Positive Youth Development, Life Satisfaction and Problem Behaviour among Youths in Malaysia - Mahadzirah, Mohamad; Mustafa, Mamat; Morliyati, Mohammad (IDOSI Publications, 2014)
The main purpose of this paper is to examine the relationships among positive development, life satisfaction and problem behaviour. Promoting positive development influences youths to achieve life satisfaction and refrain them from becoming involved in problem behaviour activities. Data was collected amongst youth participating in the youth programmes organized by the Ministry of Youth and Sport at five different locations. The selection of respondents was performed using area and systematic sampling technique. The data was collected using self- administered questionnaires comprising items to measure constructs in the study on a 10-point agreement and disagreement scale. Positive youth development was measured using items developed by Shek et al. [1] and life satisfaction was measured using Satisfaction With Life Scale (SWLS) developed by Diener et al. [2]. The items to measure problem behaviour were adapted from [3]. The final part of the questionnaire contained items pertaining to respondent’s demographic characteristics. The data was analysed using Structural Equation Modelling (SEM). The findings of the study suggested that positive youth development was manifested by self-determination, bonding, pro-social norms and social competence. Problem behaviour was measured by substance abuse and intention to engage in problem behaviour. Moreover, the findings of the study supported the proposed hypothesis that positive development has positive relationship with life satisfaction and life satisfaction has negative relationship with problem behaviour. The findings also suggested that youths with higher level of positive development are more satisfied with life.